PENGARUH PENGGUNAAN APLIKASI MYOB TERHADAP KETERAMPILAN MAHASISWA PADA MATA KULIAH KOMPUTER AKUNTANSI JURUSAN PENDIDIKAN EKONOMI KONSENTRASI AKUNTANSI ANGKATAN 2022 UNIVERSITAS NEGERI GORONTALO - Nurrahmaniya Kadir; Agil Bahsoan; Rierind Koniyo (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyse the influence of the use of the MYOB accounting application on students’ skills in the Accounting Computer course within the Accounting Concentration of the 2022 cohort at the Department of Economic Education, Universitas Negeri Gorontalo.Methods: This study employs a quantitative, survey-based approach. The data used are primary data collected through the distribution of questionnaires to students of the Economic Education Department, Accounting Concentration, Class of 2022 at Gorontalo State University. The total sample consists of 57 students. The data analysis technique used in this research is simple linear regression, with assistance from SPSS.Results: Based on the analysis, the use of the MYOB application has a significant effect on students’ skills in the Accounting Computer course within the Accounting Concentration of the 2022 cohort at the Department of Economic Education, Universitas Negeri Gorontalo. The analysis shows an R-Square value of 0.253, which indicates that 25.3% of the variability in students’ skills in the Accounting Computer course can be explained by the use of the MYOB application. Meanwhile, the remaining 74.7% is influenced by other variables not examined in this study.Conclusion and suggestion: These findings highlight the importance of integrating MYOB-based learning to enhance students’ technical and practical accounting competencies. Strengthening the implementation of computerized accounting practicum is recommended to optimize student proficiency and readiness for professional challenges. Keywords: Accounting Computer, MYOB, Student Skills, Technology-Based Learning